Host regulation of liver fibroproliferative pathology during experimental schistosomiasis via interleukin-4 receptor alpha. - Justin Komguep Nono; Hlumani Ndlovu; Nada Abdel Aziz; Thabo Mpotje; Lerato Hlaka; Frank Brombacher (Public Library of Science (PLoS), 2017)
Interleukin-4 receptor (IL-4Rα) is critical for the initiation of type-2 immune responses and implicated in the pathogenesis of experimental schistosomiasis. IL-4Rα mediated type-2 responses are critical for the control of pathology during acute schistosomiasis. However, type-2 responses tightly associate with fibrogranulomatous inflammation that drives host pathology during chronic schistosomiasis. To address such controversy on the role of IL-4Rα, we generated a novel inducible IL-4Rα-deficient mouse model that allows for temporal knockdown of il-4rα gene after oral administration of Tamoxifen. Interrupting IL-4Rα mediated signaling during the acute phase impaired the development of protective type-2 immune responses, leading to rapid weight loss and premature death, confirming a protective role of IL-4Rα during acute schistosomiasis. Conversely, IL-4Rα removal at the chronic phase of schistosomiasis ameliorated the pathological fibro-granulomatous pathology and reversed liver scarification without affecting the host fitness. This amelioration of the morbidity was accompanied by a reduced Th2 response and increased frequencies of FoxP3+ Tregs and CD1dhiCD5+ Bregs. Collectively, these data demonstrate that IL-4Rα mediated signaling has two opposing functions during experimental schistosomiasis depending on the stage of advancement of the disease and indicate that interrupting IL-4Rα mediated signaling is a viable therapeutic strategy to ameliorate liver fibroproliferative pathology in diseases like chronic schistosomiasis.